2011
DOI: 10.1063/1.3609239
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic heat flux experiments in Cu67.64Zn16.71Al15.65: Separating the time scales of fast and ultra-slow kinetic processes in martensitic transformations

Abstract: Heat treatment induced martensitic accommodation and adaptive anisotropy in melt spun Ni55Mn22Ga23 (at. %) ribbons J. Appl. Phys. 112, 103512 (2012) Modulated structure in the martensite phase of Ni1.8Pt0.2MnGa: A neutron diffraction study Appl. Phys. Lett. 101, 171904 (2012) Martensitic and magnetic transformation in Mn50Ni50−xSnx ferromagnetic shape memory alloys J. Appl. Phys. 112, 083902 (2012) Ellipsometry applied to phase transitions and relaxation phenomena in Ni2MnGa ferromagnetic shape memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Starting with the Barkhausen analysis of magnetization jumps in slowly magnetized ferromagnetics, the concept of crackles with a broad (power-law) size distribution was generalized to crackling noise because it was found that similar phenomena are much more widespread than just in magnetism. Other fields that show crackling noises include slowly sheared granular materials (1,2), slowly compressed and collapsing porous materials (3,4,5,6), plastically deformed small crystals (7,8), changes in the coexistence interval of stepwise structural phase transitions (9,10), transitions in Mott insulators (11), neuronal networks (12), and decision-making processes (13) as well as many others. Materials applications focused initially on martensitic alloys, magnetic materials (for nondestructive materials testing), geophysical applications in earthquakes, the prediction of collapses of mine shafts, breaking of porous building materials, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with the Barkhausen analysis of magnetization jumps in slowly magnetized ferromagnetics, the concept of crackles with a broad (power-law) size distribution was generalized to crackling noise because it was found that similar phenomena are much more widespread than just in magnetism. Other fields that show crackling noises include slowly sheared granular materials (1,2), slowly compressed and collapsing porous materials (3,4,5,6), plastically deformed small crystals (7,8), changes in the coexistence interval of stepwise structural phase transitions (9,10), transitions in Mott insulators (11), neuronal networks (12), and decision-making processes (13) as well as many others. Materials applications focused initially on martensitic alloys, magnetic materials (for nondestructive materials testing), geophysical applications in earthquakes, the prediction of collapses of mine shafts, breaking of porous building materials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically meaningful data can be obtained if the cooling rate is slow enough to allow the detection of individual jerks without significant overlap between them. This is achieved for cooling rates of 0.005 K/h, with faster rates showing overlap and corrupted line profiles(10).…”
mentioning
confidence: 99%
“…The use of driven systems to generate high twin densities is motivated by the experimental observation of noise generation by moving twin boundaries31–35 and the crossover from classical criticality to self‐organized criticality in driven systems 36. Hard driving (where the strain is prescribed) leads to a collapse of the mono‐domain state at the yield stress into a highly structured, mesoscopic twin pattern which remains relatively stable under increasing strain.…”
mentioning
confidence: 99%
“…The fine structure can only be observed under much lower heating rates, and such types of investigations are rare in the literature [1,[6][7][8]. Nevertheless if the scanning rate was slow enough (on the order of 0.1 K/h) the separation of the smooth base line from the individual spikes was successful in a Cu based (Cu 67.64 Zn 16.71 Al 15.65 ) alloy [1,7,8]. Statistical analysis of events showed that energy distribution followed a power law [1],…”
Section: Introductionmentioning
confidence: 99%